Diagnosis and treatment of hereditary hemochromatosis: an update. (August 2013) - Kanwar, Pushpjeet; Kowdley, Kris V
Hereditary hemochromatosis is an inherited iron overload disorder caused by inappropriately low hepcidin secretion leading to increased duodenal absorption of dietary iron, most commonly in C282Y homozygous individuals. This can result in elevated serum ferritin, iron deposition in various organs and ultimately end-organ damage, although there is incomplete biochemical and clinical penetrance and variable phenotypic expression of the HFE mutation in hereditary hemochromatosis. An elevated SF <1000 µg/l is associated with an increased risk of cirrhosis and mortality in C282Y homozygotes. Conversely, a SF <1000 µg/l is associated with a very low likelihood of cirrhosis, making liver biopsy unnecessary among C282Y homozygotes in the absence of concomitant risk factors for liver disease. Phlebotomy remains the mainstay of treatment and new treatments being studied include erythrocytapheresis and 'mini-hepcidins'. Iron overload is being recognized to play a carcinogenic role in hepatocellular carcinoma and other cancers, possibly supporting iron depletion in these patients.